Estimating the risk of suicide associated with mental disorders: A systematic review and meta-regression analysis - Moitra, Modhurima; Santomauro, Damian; Degenhardt, Louisa; Collins, Pamela Y.; Whiteford, Harvey; Vos, Theo; Ferrari, Alize (Journal of psychiatric research, 2021)
Mental disorders (MDs) are known risk factors for suicide. This systematic review updates the evidence base for this association and improves upon analytic approaches by incorporating study-level and methodological variables to account for measurement error in pooled suicide risk estimates. A systematic review was conducted to review studies on MDs as risk factors for suicide. Relevant studies were searched using PubMed, Embase, PsychINFO, and existing reviews from 2010 to 19. Studies were eligible if they were longitudinal/case-control studies, representative of the general population, used diagnostic instruments, and quantified suicide risk. The outcome assessed was relative risks (RRs) for suicide due to MDs. A multi-level meta-regression approach was used to obtain pooled RRs adjusted for covariates and between-study effects. We identified 20 eligible studies yielding 69 RRs. Disorder type, age, sex, use of psychological autopsy, study design, and adjustment for confounders were tested as predictors of pooled suicide risk. Overall, all disorders were significant predictors of suicide with predicted adjusted RRs ranging from 4·11 [2·09, 8·09] for dysthymia to 7·64 [4·3, 13·58] for major depressive disorder. Our results indicate that MDs are important risk factors for suicide. This systematic review provides pooled RRs that have been adjusted for methodological sources of bias. Findings from our paper may inform suicide prevention strategies as part of national health agendas. •Mental disorders are important risk factors for suicide.•Differences in study methodology may contribute to over or underestimation of study-reported suicide risk.•It is important to analytically quantify sources of variation when synthesizing published evidence on suicide risk in a meta-regression framework.